2022
DOI: 10.1002/ceat.202100465
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfide Synthesis Using Waste Cooking Palm Oil via Inverse Vulcanization

Abstract: Elemental sulfur and waste cooking palm oil (WCO) are abundant industrial by-products from petrochemical and food processing industries, respectively. WCO was used as a crosslinker to prepare a high-sulfur-content polymer through inverse vulcanization. Polysulfides were generated under vigorous stirring of WCO with elemental sulfur at different temperatures, crosslinking ratios, and reaction times. The physicochemical properties of the produced polysulfides were determined and the thermal stability was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…polymeric chain during inverse vulcanisation (Nayeem et al, 2022b). It demonstrates the successful polymerisation of WCO and sulphur.…”
Section: P R E S Smentioning
confidence: 74%
See 2 more Smart Citations
“…polymeric chain during inverse vulcanisation (Nayeem et al, 2022b). It demonstrates the successful polymerisation of WCO and sulphur.…”
Section: P R E S Smentioning
confidence: 74%
“…The vinylic double bonds in the monomers break down during inverse vulcanisation and react with sulphur to form sustainable polysulphides (Chalker et al, 2019). A recent investigation done by Nayeem et al (2022) showed the use of waste cooking palm oil (WCO) in inverse vulcanisation, which created a new way to deal with the threat of environmental hazards caused by WCO (Nayeem et al, 2022b). The use of different crosslinkers, simple synthesis process, and high selectivity towards heavy metals have made the inverse vulcanised polysulphide adsorbents suitable for heavy metal wastewater treatment (Chalker et al, 2021;Nayeem et al, 2022a).…”
Section: P R E S Smentioning
confidence: 99%
See 1 more Smart Citation
“…14 The interest in the synthetic method is evidenced by the work of several research groups on the subject. [16][17][18][19][20][21] The materials obtained by this method have been employed in diverse areas: infrared imaging, 22 cathodes for Li-S batteries, 23 sorbents for oil spills, 24 metal and organic decontamination, [25][26][27][28] agriculture as a matrix for slow release fertilizers, 29,30 and as antimicrobial materials. 19,31 To obtain green polymers, it is possible to employ the inverse vulcanization reaction using a waste material (elemental sulfur) and alkenes obtained from biomass processing, renewable sources, or diverted industrial waste streams.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of inverse vulcanization, that is, the sulfur reaction with unsaturated monomers, by Pyun and coworkers, together with the use of readily available unsaturated fats, has ushered in a new age in the synthesis and applications of biodegradable and bio‐sourced polymers 14 . The interest in the synthetic method is evidenced by the work of several research groups on the subject 16–21 . The materials obtained by this method have been employed in diverse areas: infrared imaging, 22 cathodes for Li‐S batteries, 23 sorbents for oil spills, 24 metal and organic decontamination, 25–28 agriculture as a matrix for slow release fertilizers, 29,30 and as antimicrobial materials 19,31 .…”
Section: Introductionmentioning
confidence: 99%